ANALISIS KEWIRAUSAHAAN AGROINDUSTRI PANGAN LOKAL SAGU - Natelda R. Timisela; Ester D. Leatemia; Febby F. Polnaya (Faculty of Economics and Business Udayana University, 2017)
Research aims to study the characteristics of sago local food agro-industries, analyze the factors that influence entrepreneurs’ characters, and analyze the effects of entrepreneurs’ characters on the management, institutional system, and the performance of agro-industries. The research focus is on local food agroindustrial of sago. While the subject of research is entrepreneurs the processing of food products of local as key businessman in the development of business. The total population of the local sago food product entrepreneurs is 240 people. Sampling using Slovin formula (n = N / (1 + N e²) = 240 / (1 + 240 x 0,05²) = 150). Data analysis is done qualitatively and quantitatively. Qualitative analysis to describe entrepreneur character, while quantitative analysis to analyze factors influencing entrepreneurial character and influence of entrepreneur character to management, institute and performance of local food agroindustry sago. The research result shows that the characteristics of the entrepreneurs include: possessing high motivation to satisfy life necessaries; future-oriented; having good leadership skills; having a wide business network; facing the changes responsively and creatively. The index value of the five characteristics varies, ranging from 60-75 percent. The entrepreneurs’ characteristics on average category include good leadership skills, facing the changes responsively and creatively. These two characteristics still need to be improved by the businessmen in order to create better characters. Meanwhile, the highly-categorized characteristics are retained or even further improved. The SEM analysis result shows that economical and physical factors affect the entrepreneurs’ characters, whereas social factor does not give any effect. Besides, the result as well indicates that the entrepreneurs’ characters significantly influence the management, the institutional, and the performance of agro-industries. This is important to build entrepreneurial spirit in order to develop sago local food industries.